PEMBINAAN GENDING BOPONG GAYA KAYUMAS DENPASAR DI SANGGAR TABUH KEMBANG WARU DENPASAR - Ni Putu Hartini; I Nyoman Mariyana; I Gede Mawan (Institut Seni Indonesia Surakarta, 2024)
This community service activity aims to preserve one of the intangible heritage assets, namely Gending BopongGaya Kayumas Denpasar. Gending Bopong is one of the Petangkilan Gendings in the Balinese Wayang (shadowpuppet) show scene. Recently, there has been a phenomenon that Gending Bopong is rarely presented anymorebecause this game has a long structure, making it difficult to master it. This is why it is feared that this gending willbecome extinct, so coaching is needed regarding mastering drumming skills and practical mastery of the Boponggending material. The methods used are lecture, demonstration, and imitation. This coaching process goes throughseveral stages, namely: (1) socialization, (2) implementation stage, (3) stabilization phase, (4) evaluation stage,and (5) presentation of coaching results. As a result of this service activity, training participants at the SanggarTabuh Kembang Waru were able to enrich their knowledge and skills in drumming Gender Wayang and foster prideand love in the effort to maintain and develop the traditional artistic heritage.